Introducing STAF: The Saarbrücken Treebank of Albanian Fiction - Luigi Talamo (Journal of Open Humanities Data)
The present paper describes the building of STAF, a Universal Dependencies treebank for Albanian. STAF was bootstrapped using a Stanza model trained on previously unreleased data and then manually corrected by three Albanian speakers supervised by the author, who also revised all sentences. STAF focuses on the fiction genre, featuring 200 sentences selected from nine literary texts written by Albanian contemporary authors.